Ṣanʿāʾ: the origins of Abrahah’s cathedral and the Great Mosque — a water sanctuary of the old Arabian religion - Daum, Werner (Proceedings of the Seminar for Arabian Studies, 2018)
Ṣanʿāʾ originated on the agricultural land belonging to the nearby town of Shuʿūb. These fields were irrigated from a wadi that formed at the foot of Jabal Nuqum, and then flowed east-west towards the Saylah, through (what would later become) Ṣanʿāʾ. As is the case with every ancient settlement in Yemen, a sanctuary stood in its flood bed. In this case, this was near its delta, in a part of the terrain where the shrine was regularly inundated. All pre-Islamic shrines in Yemen and its cultural area (such as the Kaʿbah in Mecca) lie in such a location, that is, an area that is not safe from the waters. The sanctuary was of a type known from other places in Yemen. It consisted of two elements: the shrine itself, and two poles, one considered ’male’ and the other ’female’. The shrine still exists but it has been overlooked by scholars. It is inside the Great Mosque. It was the nucleus for Ṣanʿāʾ, Ghumdān, Abrahah’s cathedral, and for the Great Mosque. Its lintel has been carbon dated to the second century AD, but the shrine itself is older. In the tenth century AD, the denomination ’grave of the prophet Ḥanẓalah b. Ṣafwān’ was bestowed on it. The two poles, however, were removed in the mid-eighth century AD, when Abrahah’s church was demolished to make room for the extension of the Great Mosque. The two poles had been incorporated into the cathedral of which they were the true and main cult objects. The mosque preserves a considerable number of spolia from the church (columns and parts of its magnificent coffered ceiling). The ancient ’grave’ incorporated into it continues to be associated with rain.